Screening for Orthostatic Intolerance in Symptomatic Children Presenting for Concussion Care. (January 2020) - Kokorelis, Christina; Slomine, Beth; Rowe, Peter C.; Suskauer, Stacy
Following concussion, children often experience nonspecific symptoms that overlap with those of other common pediatric conditions, including orthostatic intolerance (OI). The primary goal of this study was to evaluate OI in youth presenting for clinical care for concussion and reporting symptoms frequently observed in OI. Eighty-two of 114 patients aged 10 to 22 years endorsed symptoms based on 8 screening questions, and 24 of those 82 patients met criteria for OI based on an active standing test. No screening question generated clinically useful likelihood ratios for predicting OI. The prevalence of OI in this cohort is considerably higher than estimates in the general pediatric population, suggesting a link between concussion and OI. Future work is needed to evaluate the best method of testing for OI, the natural history of OI symptoms in youth with concussion, and the response to intervention in children with both concussion and OI.